Current approaches for the treatment and prevention of influenza and acute respiratory viral infections in children - O. I. Sidorovich (Медицинский совет, 2014)
Influenza and SARS are still one of the most urgent health and social problems of our society because of the high proportion in infectious disease, the risk of severe complications, acute exacerbations of chronic diseases [1], making up 90% of all infections [3].